PERLINDUNGAN HUKUM BAGI KREDITUR PREFERENCE DALAM EKSEKUSI HAK TANGGUNGAN (STUDI PUTUSAN NOMOR 695 K/PDT/2021): Legal Protection For Preference Creditors In The Execution Of Collective Rights (Study Of Decision Number 695 K/Pdt/2021) - Irnanda Lucky Ajisaputri; Irene Eka Sihombing (Faculty of Law, Universitas Trisakti, 2024)
The protection that is guaranteed when mortgage right comes into effect is protection intended by mortgage rights law. Formulation of problem in this research is (1) What is legal protection for Bank Rakyat Indonesia as the preferred creditor, (2) What is the judge's decision in the case of debtor in default in Decision Number 695 K/Pdt/2021. This research includes normative juridical which is descriptive in nature. Results of research and discussion are that legal protection for BRI as the preferred creditor is regulated by Article 6 of Law Number 4 of 1996 and punishes Halim Peace and Serli to pay principal arrears for credit facility for month of September 2019 amounting to IDR 1,320,590,708.00. Conclusion is that legal protection for creditors is provided through Law Number 4 of 1996 Article 6, Article 20 and Article 21 and in Decision Number 695 K/Pdt/2021, judge rejected plaintiffs' lawsuit against debtor in default, allowing the execution of an auction for disputed object in accordance with Article 6 of Law Number 4 of 1996 concerning Mortgage Rights over Land, and ordered payment of principal and interest arrears by debtor to PT. BRI, and ordered cassation applicant to pay court costs amounting to IDR 500,000.00.